Mapping Environmental Hidden Curriculum in Physics Learning - Yumelda Marzuki; Desnita Desnita (Jurnal Penelitian Pendidikan IPA, 2023)
Environmental problems that occur today have reached an alarming level. Global warming, flooding in the rainy season, and summer drought are environmental problems troubling people. These problems result from human behavior that is not wise in managing the environment. The trigger for this problem is human behavior, so the solution is to change behavior. Changes in human behavior toward the environment can be done by integrating various subjects, such as a "Hidden Curriculum." One of the subjects that can integrate environmental education is high school physics. For the integration to be right on target, it is necessary to design a curriculum. It is necessary to create a matrix of integration of education in learning senior high school vision. This article was written to convey the results of research in the form of environmental integration design in class XI semester two high school physics learning, mapping subject matter, and environmental competencies. The results obtained are in the form of an integration matrix. This matrix becomes a reference for developing programs and learning tools for implementing environmental education integration in physics learning class XI, semester 2. To achieve the objectives, qualitative research methods are applied